Curriculum, Deaf Protagonism and Emancipation - Ruzza, Mara Lopes Figueira de (2022)
This Article aims to discuss how the Deaf Protagonism, considered central in the Curriculum, can contribute to the process of raising awareness of the Deaf Subject, breaking with the logic imposed by historical, cultural and political constructions. Taking as a reference a critical and democratic education that considers the effective participation of the Deaf as essential, bibliographical references are presented that support the reflections on the relevance of meaning the linguistic, cultural and epistemological difference of the Deaf Community as a guarantee of the Deaf Subject's right to a dignified demand.